Aktivitas antioksidan dengan metode cuprac dan penetapan kadar fenolat total pada ekstrak dan fraksi makroalga Eucheuma cottonii - Kurnia, Dewi; Rohmah, Desita; Anggraeni, Vina Juliana (Jurnal Agrotek Ummat, 2022)
Antioxidants are compounds that can counteract free radicals. The macroalgae Euchema cottonii belongs to a type of seaweed from the Rhodophyta which is thought to have antioxidant activity. In this study, the antioxidant activity was tested using the CUPRAC method using spectrophotometry at 450 nm and the determination of total phenolic compounds in the extract and macroalgae fraction Eucheuma cottonii using the Folin Ciocalteu method. The extraction method was carried out using the maceration method with 70% ethanol and fractionation using ECC with n-hexane, ethyl acetate, and methanol-water (20% v/v). The results of TLC monitoring of Eucheuma cottonii showed the presence of flavonoid compounds, phenols, alkaloids, steroids, and triterpenoids. The results of the antioxidant activity test showed that the EC50 for the ethanol extract and the n-hexane, ethyl acetate, and methanol-water fractions were 89.11; 143.40; 100.02 and 90.22 g/ml respectively with EC50 vitamin C as a comparison of 6,86 g/ml. The results of the determination of the total phenolate content of the ethanol extract and the fractions of n- hexane, ethyl acetate, and methanol-water were 2.77; 1.96; 2.76; and 3.09 mg/GAE per 100 mg extract. The ethanol extract had a strong antioxidant activity with an EC50  89.11 g/ml and the highest total phenol content was in the methanol-water fraction of 3.09 mg/GAE per 100 mg extract. The results showed that the ethanolic extract of the macroalga Eucheuma cottonii has the potential as an alternative source of antioxidants.